A Bigger Bang for a Bigger Buck: What China's Changing Attitude Toward UN Peacekeeping Says About Its Evolving Approach to International Institutions. Issue 2 (20th December 2016) - Sun, Meicen
Abstract: While China used to condemn UN peacekeeping as a Western tool in the 1970s, it now supplies the largest number of UN peacekeeping troops among the UN Security Council Permanent Five. To explain this puzzling change in China's attitude toward UN peacekeeping, this paper constructs an original framework that unpacks China's evolution in self-identity as a "responsible major power" by first disaggregating the economic, military, and political costs and benefits for its participation in UN peacekeeping. In so doing, this paper shows that China's attitudinal change is best captured by a shift from a present-cost-driven, "purchase" model of participation in international institutions to a future-benefit-driven, "investment" model of participation. A series of key events that occurred between the mid-1990s and the early 2000s, notably China's accession to the WTO and its successful bid to host the 2008 Olympic Games, had in part accustomed China to paying large institutional costs upfront in order to be "part of the club." The paper concludes with a brief discussion on the applicability, or the lack thereof, of the Chinese experience to other countries' experiences with international institutions given China's unique historical trajectory and cultural idiosyncrasies.